MIGRATION AND THE EFFECTS ON PUBLIC HEALTH: MIGRACIÓN Y LOS EFECTOS EN LA SALUD PÚBLICA - Loayza Alarico, Manuel J. (2019)
Between 2000 and 2017, the number of international migrants was 173 to 258 million, representing a 49% increase in this period. In America, since October 2018, the migratory flow of nearly three million Venezuelans has been intensified; with about 1.7 million migrants(representing about 70% of the migration) being received in the countries of Colombia, Peru and Ecuador. In Peru since 2016, the flow of Venezuelans to the country has increased, from 6,615 residents in that year to 728,120 at the end of March 2019, being the most important migratory wave of the 21st century in Peru, turning it into the second country in the world to host the largest number of immigrant Venezuelans after Colombia. Currently, Venezuelans constitute the biggest foreign community in Peru.